Rancang Bangun Simulasi Sistem Monitoring Temperatur dan Humidty Data Center Berbasis Internet of Things (IOT) - Iswidodo Iswidodo (Syntax Idea)
This research report discusses how to create a system for monitoring temperature and humidity in a data center and remotely controlling a relay. The research report titled "Design and Implementation of a Simulation System for Monitoring Temperature and Humidity in a Data Center Based on Internet of Things (IoT)" can be used for monitoring using a Web Interface. A MYSQL database is utilized to store data for displaying the monitoring screen and controlling relays, which can be accessed through users' mobile phones or computers. The main function of this system is to control the temperature and humidity in the data center and operate remote control relays from accessible sites. The main components used to create this system include the ESP8266 Wemos D1 Mini as the main control unit of the system, which can directly connect to the internet via WiFi connection. The system also incorporates a DHT11 sensor and a 4-channel 5VDC relay module.